Improvement of chromium biosorption through protoplast electrofusion between Candida tropicalis and Candida lipolytica - He, Bao-yan; Yin, Hua; Yang, Feng; Ye, Jin-shao; Peng, Hui; Lu, Xian-yan; Zhang, Na (Journal of Central South University, 2012)
Protoplasts from Candida tropicalis and Candida lipolytica were fused under an optimized electrofusion (electrical pulse strength 6 kV/cm, pulse duration time 40 μs and pulse times 5) and then regenerated on YEPD media for achieving new genotypes with higher chromium loading capacity. A target fusant RHJ-004 was screened out by its chromium resistance and chromium-sorbing capacity tests for further research. The comparative study of applicability shows that the fusant has better performance than its parent strains in respect of solution pH, biomass concentration and chromium loading capacity. Especially for treating low concentration Cr(VI) (≤20 mg/L), above 80% chromium is sequestered from the aqueous phase at pH 1–9. Atomic force microscopy (AFM) visualizes the distribution of chromium on the binding sites of the cells, suggesting that the altered surface structure and intracellular constitutes of the fusant associate with its increased biosorption capacity. The rapid biosorption processes of chromium follow the Langmuir model well.